2011
DOI: 10.1002/app.34164
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and energy of activation of the melting of poly (ε‐caprolactone) with and without prior treatment with span 80

Abstract: Differential scanning calorimetry (DSC) is used to determine the energy of activation and melting mechanism of PCL and of mixtures of PCL with the surfactant Span 80. The melting of poly(ecaprolactone) follows a nucleation and growth model with an Avrami exponent of 4. Addition of Span 80 reduces the energy of activation of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A p and E p stand for the pre‐exponential constant and the activation energy of the melting, respectively. [ 18 ] The material properties and the parameters entered in the cure and melting kinetics models used in the present study are summarized in Tables 1 and 2 , respectively. When compared with experiments, an additional heat loss term − H loss ∙ ( T − T 0 ) was added to the left‐hand side of the first equation in Equations () and (), where H loss = 24.5 kW m −3 is the heat loss coefficient and was determined by fitting the local temperature history in experiments (Figure S9, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…A p and E p stand for the pre‐exponential constant and the activation energy of the melting, respectively. [ 18 ] The material properties and the parameters entered in the cure and melting kinetics models used in the present study are summarized in Tables 1 and 2 , respectively. When compared with experiments, an additional heat loss term − H loss ∙ ( T − T 0 ) was added to the left‐hand side of the first equation in Equations () and (), where H loss = 24.5 kW m −3 is the heat loss coefficient and was determined by fitting the local temperature history in experiments (Figure S9, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Koocheki et al reported a reduction in the T g of PLGA due to the interaction between the Tween 80 and polymer molecules 39 . Fraga‐López et al demonstrated the plasticizer effect of Span 80 when studying the influence of this surfactant in the melting activation energy of poly(ε‐caprolactone) 45 …”
Section: Resultsmentioning
confidence: 99%
“…39 Fraga-López et al demonstrated the plasticizer effect of Span 80 when studying the influence of this surfactant in the melting activation energy of poly(ε-caprolactone). 45 Carefully observing the results shown in Figure 13, it was noticed that the T g of PLLA microparticles produced with Span 80 were lower than those produced with Tween 80. A more intense plasticizer effect was expected when using Span 80 instead of Tween 80 due to the low HLB (4.3) of Span 80, which characterizes it as a hydrophobic compound.…”
Section: Thermal Characterization Of the Microparticlesmentioning
confidence: 85%
“…The solution in discrete phase-changing PCL particles (denoted hereafter with the subscript p) is obtained with the aid of the following melting–diffusion model describing the evolution of the degree of melting δ In the first equation, H p denotes the melting enthalpy and the negative sign reflects the endothermic nature of the melting process. The second equation approximates the phase transition of the PCL as a first-order kinetic model, where A p and E p , respectively, stand for the pre-exponential constant and the activation energy of the melting process. , The thermal properties and melting kinetics parameters are listed in Tables and , respectively.…”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…The second equation approximates the phase transition of the PCL as a first-order kinetic model, where A p and E p , respectively, stand for the pre-exponential constant and the activation energy of the melting process. 37,39 The thermal properties and melting kinetics parameters are listed in Tables 1 and 2, respectively. Equations 1 in the COD resin and eq 3 in the part of the domain occupied by the embedded PCL particles are solved in the rectangular domain shown schematically in Figure 2a while maintaining the particle volume fraction ϕ fixed (ϕ = 0.1).…”
Section: ■ Introductionmentioning
confidence: 99%